2016
DOI: 10.1124/dmd.115.066522
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Flutamide-Bioactivation and Oxidative Stress In Vitro and In Vivo

Abstract: The nonsteroidal androgen-receptor antagonist flutamide is associated with hepatic injury. Oxidative stress and reactive metabolite formation are considered contributing factors to liver toxicity. Here we have used flutamide as a model drug to study the generation of reactive drug metabolites that undergo redox cycling to induce oxidative stress (OS) in vitro and in vivo. Lipid peroxidation (LPO) markers, as well as genes regulated by the redox-sensitive Nrf2 pathway, have been identified as surrogates for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Increased MDA level indicated destruction of lipid macromolecules included in the biological membranes which led to structural and functional alterations of hepatic cells, that ultimately caused hepatotoxicity (Xie et al, 2014). Present finding is consistent with published in vitro and in vivo studies which demonstrated increase in LPO products in hepatocytes and plasma of rats after treatment with FLU (Al Maruf and O'Brien, 2014;Teppner et al, 2016). Also, treatment of rat primary hepatocytes with FLU resulted in a high reactive oxygen species (ROS) production and complete GSH depletion (Leclerc et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Increased MDA level indicated destruction of lipid macromolecules included in the biological membranes which led to structural and functional alterations of hepatic cells, that ultimately caused hepatotoxicity (Xie et al, 2014). Present finding is consistent with published in vitro and in vivo studies which demonstrated increase in LPO products in hepatocytes and plasma of rats after treatment with FLU (Al Maruf and O'Brien, 2014;Teppner et al, 2016). Also, treatment of rat primary hepatocytes with FLU resulted in a high reactive oxygen species (ROS) production and complete GSH depletion (Leclerc et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…Published data reported that FLU bioactivation using CYP1A2 generated a nitro anion free radical (Vazquez et al, 2004). These radicals can bind covalently to proteins and lipids, or remove hydrogen atoms from polyunsaturated fatty acids in lipids, leading to induction of LPO and subsequently hepatocyte injury (Williams and Burke, 2000;Teppner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding on the reduction of HO-1 and NQO1 levels in both 143B and MG63 cells demonstrated the consequent effects of knocking down NRF2 on NRF2-regulated gene expression by bioengineered NRF2-siRNA. Furthermore, a higher accumulation of intracellular ROS highlighted the impact of interfering NRF2/HO-1 axis on redox homeostasis (DeNicola et al, 2011;Teppner et al, 2016). In addition, the change of cellular ROS levels following the perturbation of NRF2/HO-1 axis should provide at least partial explanation for the antiproliferative activity of bioengineered NRF2-siRNA against OS cells, as well as the improved cell sensitivity to doxorubicin, cisplatin, and sorafenib.…”
Section: Discussionmentioning
confidence: 98%
“…The HO-1 enzyme is one of the main targets of NRF2 and a major effector of NRF2-dependent cell response to oxidative stress and xenobiotics (Teppner et al, 2016). A concurrent upregulation of NRF2 and HO-1 is obvious in many types of tumors and correlates well with tumor progression, resistance to therapy, and clinical outcomes (Furfaro et al, 2016).…”
Section: Discussionmentioning
confidence: 99%